On the links between sea level and temperature variations in the Chesapeake Bay and the Atlantic Meridional Overturning Circulation (AMOC) - Tal Ezer; Teresa Updyke (Ocean Dynamics, 2024)
Recent studies found that on long time scales there are often unexplained opposite trends in sea level variability between the upper and lower Chesapeake Bay (CB). Therefore, daily sea level and temperature records were analyzed in two locations, Norfolk in the southern CB and Baltimore in the northern CB; surface currents from Coastal Ocean Dynamics Application Radar (CODAR) near the mouth of CB were also analyzed to examine connections between the CB and the Atlantic Ocean. The observations in the bay were compared with daily Atlantic Meridional Overturning Circulation (AMOC) observations during 2005–2021. Empirical Mode Decomposition (EMD) analysis was used to show that variations of sea level and temperature in the upper and lower CB are positively correlated with each other for short time scales of months to few years, but anticorrelated on low frequency modes representing decadal variability and long-term nonlinear trends. The long-term CB modes seem to be linked with AMOC variability through variations in the Gulf Stream and the wind-driven Ekman transports over the North Atlantic Ocean. AMOC variability correlates more strongly with variability in the southern CB near the mouth of the bay, where surface currents indicate potential links with AMOC variability. For example, when AMOC and the Gulf Stream were especially weak during 2009–2010, sea level in the southern bay was abnormally high, temperatures were colder than normal and outflow through the mouth of CB was especially high. Sea level in the upper bay responded to this change only 1–2 years later, which partly explains phase differences within the bay. A persistent trend of 0.22 cm/s per year of increased outflow from the CB, may be a sign of a climate-related trend associated with combination of weakening AMOC and increased precipitation and river discharge into the CB.